COMPARISON OF POSITIVITY OF TUBERCULIN SKIN TEST WITH DIAGNOSTIC BCG IN CHILDREN SUFFERING FROM TUBERCULOSIS - Alam, Tariq; Abbas, Zaheer; Gillani, Saima; Mustafa, Syed Hassan; Ali, Syed Maisam; Khan, Mehreen (Journal of Ayub Medical College Abbottabad, 2020)
Background: Tuberculosis is major public health problem in Pakistan and it is often unrecognized cause of morbidity and mortality in children living in endemic areas. Children with age less than 5 years, and especially those who are immune compromised, are at higher risk of developing tuberculosis following exposure. Tuberculosis in children is usually difficult to diagnose compare to adult patients due to its atypical presentation. Tuberculin skin test and Bacille Calmette-Guerin (BCG) are widely used as diagnostic tests for tuberculosis. It was a Cross sectional study carried out from May 2017 to Nov 2018 in the department of Paediatrics, Ayub Teaching Hospital Abbottabad. Methods: Both BCG and tuberculin skin test were performed at the same time by the same doctor. Personal data like age, gender and address, type of tuberculosis, positivity of tuberculin skin test and positivity of diagnostic BCG were recorded. The induration was read 48-72 hours after administration. Results: As per frequencies and percentages for positivity of tuberculin skin, 51 (67.10%) patients showed positivity for tuberculin skin while 71 (93.42%) patients showed positive results via BCG Test. Conclusion: In paediatric age group, diagnostic BCG test has got better diagnostic value over Tuberculin Skin Test in diagnosis of tuberculosis. Keywords: Tuberculin Skin Test; BCG Test; Pulmonary Tuberculosis